Challenges faced by air cargo road feeder services (Truck flight): a case of MASkargo, KLIA / Muhammad Mulup - Mulup, Muhammad (Faculty of Business and Management, 2010)
The truck flight business is one of the most lucrative business segments for logistics industry. This study is to explain the challenges of truck flight as a feeder air cargo road services faced by MASKargo Sdn. Bhd. There are several methods will be used such by interview, documentation and observation to explain the challenges. Gap analysis will be done and the findings perhaps can be used by the researchers to help give suggestion to MASkargo Sdn. Bhd. Thus, adjustment to improve their services and solve the challenges they faced. The conclusion of this study is outcome of this study.